2008
DOI: 10.1007/s00438-008-0361-2
|View full text |Cite
|
Sign up to set email alerts
|

Computational identification of transcription frameworks of early committed spermatogenic cells

Abstract: It is known that transcription factors (TFs) work in cooperation with each other to govern gene expression and thus single TF studies may not always reflect the underlying biology. Using microarray data obtained from two independent studies of the first wave of spermatogenesis, we tested the hypothesis that co-expressed spermatogenic genes in cells committed to differentiation are regulated by a set of distinct combinations of TF modules. A computational approach was designed to identify over-represented modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…The overlap of RNA‐Seq and qPCR assay results validated LHS‐dependent testicular gene expressions in buntings. In LD states, we found an increased HOOK1 expression, consistent with its role in spermatid differentiation (Chen et al, ), and a decreased RGS2 expression, consistent with its downregulation with the transition from spermatogonia to spermatocyte stage in murine spermatogenesis (Lalancette, Platts, Lu, Lu, & Krawetz, ). We also found high CYFIP2 mRNA expression in both LDES and LDLS, although the levels were still significantly lower in former than the latter state.…”
Section: Discussionsupporting
confidence: 83%
“…The overlap of RNA‐Seq and qPCR assay results validated LHS‐dependent testicular gene expressions in buntings. In LD states, we found an increased HOOK1 expression, consistent with its role in spermatid differentiation (Chen et al, ), and a decreased RGS2 expression, consistent with its downregulation with the transition from spermatogonia to spermatocyte stage in murine spermatogenesis (Lalancette, Platts, Lu, Lu, & Krawetz, ). We also found high CYFIP2 mRNA expression in both LDES and LDLS, although the levels were still significantly lower in former than the latter state.…”
Section: Discussionsupporting
confidence: 83%
“…Several zinc finger domain encoding RNAs have been observed that include a range of binding domains, e.g., C2H2 and GATA DNA binding, CCHC single strand RNA binding, and PHD and RING protein binding domains. Binding sites for their interactions as part of transcriptional frameworks have been identified in genes that are active during spermatogenesis (Lalancette et al 2008). Other transcripts retained specifically in sperm with known roles in embryogenesis encode for protein components of the centrosome (CEP85L and KIAA0101), extraembryonic structures (SLC38A7) or those regulating events during early embryogenesis (NNAT and PTK7).…”
Section: Spermatozoal Retained Rnasmentioning
confidence: 99%
“…Therefore, whereas spermatozoa are produced asynchronously during postpubertal life, germ cells differentiate synchronously during the first wave of spermatogenesis. Hence, prepubertal testes of a given age have homogeneous contents, and comparing the transcriptome contents of gonads at different ages allowed the identification of stage-specific transcripts [5] , [6] , and putative transcriptional networks were proposed from these data [7] .…”
Section: Introductionmentioning
confidence: 99%